48 hours - Forstchen, William R (Tom Doherty Associates, 2019)
"From the author of the smash hit, New York Times bestselling One Second After series comes a thriller in which the survival of humanity itself is at stake. The countdown is on. In less than forty eight hours, Earth will be hit by a major solar storm. At first, it is thought to be a Coronal Mass Ejection (CME) that will severely damage our world's electronic infrastructure. A crisis to be certain, but one that can be survived--until something far more frightening is discovered by NASA's solar observation teams. It is not just a CME. The sun is about to let loose with a solar explosion of such intensity it will result in an ELE, an "Extinction Level Event." A final hour might be approaching that could see the near extinction of all life on earth. How will humanity reaction to such news? How would you react?" --